A rare case of cerebellar toxicity after prolonged use of metronidazole: a case report - Panchal, Yash N.; Patel, Maitri M.; Patel, Mukundkumar V. (International Journal of Research in Medical Sciences, 2022)
Metronidazole, a commonly used antiprotozoal and antibacterial medication is usually a safe and rarely reported to cause serious side effects. Major nervous side effects are peripheral ones, while central toxicity is rare. Following the discontinuation of the medication, clinical improvement is seen in the most cases. A 62 years old female patient was presented to hospital after experiencing the symptoms of an unsteady gait, difficulty in walking, impaired coordination of arms and legs, slurring of the speech, headache, tingling and numbness of both the feet and ascending limb weakness following intake of 400 mg metronidazole TDS daily for 2 months. The motor system examination revealed reduced muscle power, and DTR (Deep tendon reflex) was found to be 2+, except ankle reflex absent, while examination of sensory system showed, decrease pain and joint vibration sense up to the neck with absent planter reflex. The axial magnetic resonance imaging study of the brain showed bilateral symmetric hyperintensity involving both dentate nuclei in FLAIR image. The patient’s clinical conditions, on the other hand was deteriorated even after the discontinuation of the medication, hence injection methylprednisolone was given as an empirical therapy and was proved to be successful, and patient was recovered completely.